Shear bond strength of metallic brackets bonded to enamel pretreated with Er,Cr:YSGG LASER and CPP-ACP - Yomna A. Nabawy; Tarek N. Yousry; Nadia M. El-Harouni (BMC, 2021)
Abstract Background Increased risk of enamel demineralization during and after orthodontic treatment raises the demand for better preventive measures including combinations of laser, CPP-ACP, and fluoride. The combination of Er,Cr:YSGG laser with CPP-ACP was proved to have a synergetic effect compared to each of them alone. Shear bond strength (SBS) of orthodontic brackets bonded to the enamel surface after being treated with preventive measures is critical. The aim of this study was to compare the SBS and failure mode of metallic brackets bonded to teeth with no pretreatment and pretreated enamel surface, either with Er,Cr:YSGG laser alone or combined with CPP-ACP. Methods Sixty sound extracted human premolar teeth were allocated randomly to 3 groups: In Group 1 (control), teeth were etched and bonded directly; in Group 2, laser pretreatment of the enamel surface was done followed by etching and bonding as in the control group; in Group 3, the enamel surface was lased then CPP-ACP was applied according to the manufacturer instructions, etched and bonded. SBS and Adhesive remnant index (ARI) were evaluated. Results No significant differences were found between the 3 groups neither in the SBS nor in the ARI scores. Conclusions The use of combined Er,Cr:YSGG laser with CPP-ACP as a preventive measure before bonding orthodontic brackets does not endanger the bracket's bonding strength.